Improving Students’ Speaking Skill by Using Mind Mapping Teaching Media - angel sophia intan (Riwayat: Educational Journal of History and Humanities, 2023)
This research is attracted by a situation where the students’ have no idea to speak in public or unable to convey the message to the listeners effectively, speaking skill still using long note and teaching media that do not help enough the students to speak well. This research aims to improve students’ speaking skill at XI IPS 1 SMAN 9 Bungo. The purposes becoming more creative and can easily remember what to say in front of their classmate by using mind mapping teaching media. This research was classroom action research. The actions are implemented in two cycles based on the class schedule. This research involved the 21 students of class XI IPS 1 SMAN 9 Bungo in the academic year of 2020/2021 and the English teacher as the research collaborator. The data of the study were in the forms of qualitative and quantitative data. The result shows that there are increasing of students’ in speaking skill. In the first cycle, it can be known that among 21 students’ who got scores pass the school standard KKM is 9 students’ or 43% meanwhile students’ which do not complete yet is 12 students or 57%. Meanwhile, in the second cycle it can be seen that among of 21 students’ who got scores above than the standard criteria minimum is 16 students’ or 76% meanwhile students’ which do not complete yet is 5 students or 24%.